Properties of eco-friendly composite from recycled polypropylene - Samat, Noorasikin; Mokhtar, Wan Nur Athirah; Zulkifli, Nur Izzati (2014)
The recycled polypropylene (rPP) usually exhibits low mechanical property compared to virgin polypropylene. Microcrystalline cellulose (MCC) fiber may improve the mechanical property of rPP. The mechanical and water uptake properties of rPP composites filled with MCC was studied. Different composition of rPP composites (2,5,10,20 and 40wt%) and a constant MAPP coupling agent (3wt%) were prepared with injection molding after compounded in extruder machine. It was shown that the presence of MCC decreased the mechanical properties particularly at high content of MCC fiber, excluding the Young modulus. rPP composites with MAPP show higher mechanical properties. Water uptake property also exhibited a similar trend. Improvement in the interfacial adhesion between fiber-matrix is evident from FESEM analysis which supports the mechanical results.